Economic costs of rabies post-exposure prophylaxis and healthcare utilization patterns post animal bites: An experience from a private healthcare facility in Bhubaneswar, Odisha, India - Das Ayesha; Singh Snigdha; Bhowmick Sneha; Mohapatra Ipsa (Journal of Family Medicine and Primary Care)
Introduction: Rabies remains a public health challenge in many parts of the world, particularly in countries like India, where it is responsible for a significant number of human fatalities. Despite being a preventable disease, rabies continues to exert a heavy toll on the population, largely due to delays in seeking post-exposure prophylaxis (PEP) and the economic burden associated with treatment. Objective: 1. To address this gap by assessing the economic costs of rabies PEP and healthcare utilization patterns among individuals treated at a private healthcare facility in Bhubaneswar 2. To assess patient’s awareness on rabies prevention and reason for non-adherence to PEP and their psychological status and behavioral change post-bite incident. Methods: Longitudinal mixed-method study among patients who received anti-rabies vaccination in the study centre from April, 2024-July, 2024, using pre-tested questionnaire. Results: 133 animal bite exposure cases were reported. Dog bite was most common (67.86%) followed by cat bite (30.03%). 72.8% were self-motivated to seek health care. Overall, the total direct medical cost (Rs.2968 ± 1095) was higher than the total indirect cost (Rs.2160 ± 994). Those fully vaccinated spent more towards ARV (Rs.4750 ± 152, P = 0.02) and consultation (Rs.450 ± 189, P = 0.04), while participants partially vaccinated had higher lost wages (Rs.3532 ± 440, P = 0.05).72.8% reported being scared of animals post-incident 5% participants adopted preventive measures against animal bites in future. 63.5% were aware of before or to counseling at health-care facility. The association between vaccination status against rabies and awareness of the potential consequences of rabies was statistically significant (P = 0.04). 41.36% adhered to the recommended PEP doses as per schedule. PEP Non-adherence was mostly due to the high cost of treatment (88.5%). Conclusion: Financial strain was compounded by psychological and behavioral stress experienced by patients post-bite, indicating a multifaceted impact on individuals affected by animal bites. Awareness of rabies and its management was significantly better among those completing the vaccination regimen suggesting that comprehensive education ensures adherence to vaccination.